Kulturnation kontra Verfassungsnation – historyczny spór wokół obywatelstwa i narodowości w Niemczech - Hildebrandt-Wypych, Dobrochna (Studia Edukacyjne, 2020)
The almost entirely elite-driven liberalization of the right to acquire citizenship collides currently with the increasingly xenophobic sentiments and openly anti-immigrant movements among the general public all over Europe. Even in Germany discussions about the liberalization of citizenship law in the late 1990s have become a symbolic part of the dispute between supporters of ethnocentric Kulturnation (the cultural nation) and the advocates of civic Verfassungsnation (the constitutional nation). The article presents the historical context of the development of the German citizenship policy. It also raises the question of the possibility to create and legitimize – on the basis of liberalized regulations of the law on citizenship – new definitions of a symbolic membership in a civic community, located outside the traditional, ethnically based citizenship regime.